The future of academic haematology. (16th December 2016) - Hay, Deborah; Hatton, Christian S.R.; Weatherall, David J.
Summary: Recent advances in the basic medical sciences, particularly cell biology and genomics, have great promise for the future development of all aspects of haematological practice. They will also impinge on the hitherto neglected fields of haematology, including haematology involving the care of the rapidly increasing number of elderly patients and the complex problems of haematological practice in the developing countries. To obtain the maximum benefit from these new developments it will be necessary to review the patterns of training of haematologists of the future at every level. In short, it will be important to try to design and develop various career pathways for training haematologists including those who wish to work full time in basic research, combine research with clinical practice, or commit all their time to clinical work and teaching.